2008
DOI: 10.1371/journal.ppat.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Foamy Macrophages from Tuberculous Patients' Granulomas Constitute a Nutrient-Rich Reservoir for M. tuberculosis Persistence

Abstract: Tuberculosis (TB) is characterized by a tight interplay between Mycobacterium tuberculosis and host cells within granulomas. These cellular aggregates restrict bacterial spreading, but do not kill all the bacilli, which can persist for years. In-depth investigation of M. tuberculosis interactions with granuloma-specific cell populations are needed to gain insight into mycobacterial persistence, and to better understand the physiopathology of the disease. We have analyzed the formation of foamy macrophages (FMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
740
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 621 publications
(816 citation statements)
references
References 41 publications
(54 reference statements)
29
740
1
7
Order By: Relevance
“…Foamy macrophages containing multiple cholesterol loaded lipid bodies constitute a distinct trait of tuberculous granulomas and a safe haven for mycobacteria, since they have been found to harbor multiple bacilli [150,151]. Induction by mycolic acids of macrophages rich in lipid bodies was further confirmed on human monocyte-derived macrophages [152]. Here, the authors further showed that oxygenated mycolic acids, mostly of the keto class, play a leading role in the observed foamy macrophage formation.…”
Section: Cholesteroid Nature Of Mycolic Acidsmentioning
confidence: 58%
“…Foamy macrophages containing multiple cholesterol loaded lipid bodies constitute a distinct trait of tuberculous granulomas and a safe haven for mycobacteria, since they have been found to harbor multiple bacilli [150,151]. Induction by mycolic acids of macrophages rich in lipid bodies was further confirmed on human monocyte-derived macrophages [152]. Here, the authors further showed that oxygenated mycolic acids, mostly of the keto class, play a leading role in the observed foamy macrophage formation.…”
Section: Cholesteroid Nature Of Mycolic Acidsmentioning
confidence: 58%
“…It may be thought that R-Mtb shifts to dormancy within infected macrophages after having subverted their antimicrobial and APC potential (11). Additionally, M. tuberculosis may reside within subverted or foamy macrophages in mature granulomas (51,52), where T cells are physically separated from infected cells by a fibrous wall or caseum that limits APC/lymphocyte interactions (4). Lastly, M. tuberculosis may rest dormant in non-APC, representing sites of immunoprivilege (14) for M. tuberculosis persistence in LTBI.…”
Section: Discussionmentioning
confidence: 99%
“…2b, arrows) predominate in advanced TB and are only induced by virulent mycobacteria in response to oxygenated mycolic acids. 165 These cells are thought to provide a nutrient-rich, protective reservoir for Mtb persistence, as these cells have reduced microbicidal and phagocytic activity. Foamy macrophages can also induce apoptosis of Th1 cells through the Fas/Fas ligand mechanism while suppressing their own apoptosis through high expression of the antiapoptotic Bcl2 molecule.…”
Section: Cellular Responsementioning
confidence: 99%